The mathematical nature of the living world : the power of integration - Chauvet, G. (Gilbert) (World Scientific, 2005)
The topic of the book a theory of functional biology thatincorporates the fundamental principles underlying the functioning ofliving organisms is clearly appropriate as we celebrate the 50thanniversary of the discovery by Watson and Crick of the structure ofthe DNA molecule.